2012
DOI: 10.1139/f2011-155
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for sea lice-induced marine mortality of Atlantic salmon (Salmo salar) in western Ireland from experimental releases of ranched smolts treated with emamectin benzoate

Abstract: Sea trout (Salmo trutta) stock collapses in coastal areas of western Ireland subject to salmon aquaculture were contemporaneous with high abundances of larval sea lice (Lepeophtheirus salmonis) on juvenile sea trout. Whereas sea trout remain in near-shore waters throughout their marine migration, Atlantic salmon (Salmo salar) smolts typically move quickly offshore into oceanic waters. It might therefore be predicted that salmon smolts would be less vulnerable to coastal stressors and less likely to be negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 38 publications
0
60
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to present evidence of induced mortality due to salmon lice infection at the population level in anadromous brown trout. Several studies have quantified mortality in Atlantic salmon caused by salmon lice by comparing the growth and survival of groups with prophylactic chemical treatment with untreated controls (Skilbrei & Wennevik 2006;Hvidsten et al 2007;Gargan et al 2012). Gargan et al (2012) compared treated and untreated groups of salmon in eight experimental releases from three locations in western Ireland and found that treated groups were 1.8 times as likely to return as controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to present evidence of induced mortality due to salmon lice infection at the population level in anadromous brown trout. Several studies have quantified mortality in Atlantic salmon caused by salmon lice by comparing the growth and survival of groups with prophylactic chemical treatment with untreated controls (Skilbrei & Wennevik 2006;Hvidsten et al 2007;Gargan et al 2012). Gargan et al (2012) compared treated and untreated groups of salmon in eight experimental releases from three locations in western Ireland and found that treated groups were 1.8 times as likely to return as controls.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies require accurate information about return rates of smolt cohorts, and preferably also about regional infection levels. In Atlantic salmon, comparisons of return rates of smolt groups protected against salmon lice by various chemicals with untreated controls have shown that treated groups often have higher survival rates, suggesting a population-regulating effect of salmon lice (Skilbrei & Wennevik 2006;Jackson et al 2011;Gargan et al 2012). For anadromous brown trout, however, this is less well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Sea lice present during the spring smolt outmigration through Killary Harbour could have salmon farm and/or wild salmon sources. Gargan et al (2012) found that the number of wild salmonids was very low during this period, and that sea lice abundance on local farmed salmon was 3 to 4 orders of magnitude greater than the estimate for wild salmonids. A study on the production of sea lice larvae from farmed and wild salmon and its relation to the infestation of wild sea trout found that farmed salmon contributed 95% of the total production of L. salmonis nauplii in the mid-west Irish coast region (Tully & Whelan 1993).…”
Section: Discussionmentioning
confidence: 67%
“…Krkošek et al 2007). One of the mechanisms that couples increased mortality in wild salmon populations with fish farming is the increased spread and production of the salmon louse, the parasitic copepod (Lepeophtheirus salmonis), which can infect and kill salmon smolt during migration (Jackson et al 2011;Gargan et al 2012). The Hardangerfjord is one of the fjords with the highest density of salmon farms in the world (Skaala et al 2014).…”
Section: Salmonmentioning
confidence: 99%